Molecular cloning of the SMAD4 gene and its mRNA expression analysis in ovarian follicles of the Yangzhou goose (Anser cygnoides). Issue 4 (3rd July 2016) - Huang, Z.; Yuan, X.; Wang, M.; Wu, N.; Song, Y.; Chen, Y.; Zhang, Y.; Xu, Q.; Chen, G.; Zhao, W.
Abstract: Mothers against decapentaplegic homolog 4 ( SMAD4 ) is an important protein in animal reproduction. It plays pivotal roles in cellular pathways, including apoptosis. The expression profile of the SMAD4 gene in goose ovarian follicles has not been reported. In this study, the SMAD4 coding sequence was cloned from the Yangzhou goose. A phylogenetic analysis was performed and mRNA expression was examined in various tissues using quantitative real-time PCR. An alternative splice form of SMAD4, SMAD4-b having 1656 bp, was identified. SMAD4-a mRNA was widely expressed in various healthy tissues, whereas SMAD4-b was very weakly expressed. SMAD4 mRNA in the ovary and oviduct was significantly higher than that in the pituitary and hypothalamus. SMAD4 mRNA expression analysis in hierarchical follicles showed that the level of SMAD4 mRNA was higher in large white follicles and post-ovulatory follicles than in the other follicles. The results indicate that SMAD4 might be involved in the recruitment of hierarchical follicles.